1999
DOI: 10.1046/j.1365-2249.1999.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 in HIV infection: increasing serum IL-10 levels with disease progression—down-regulatory effect of potent anti-retroviral therapy

Abstract: To examine the potential pathogenic role of IL-10 in HIV infection, we measured serum IL-10 levels in 51 HIV-infected patients and 23 healthy controls both on cross-sectional and longitudinal testing. All clinical groups (Centers for Disease Control (CDC) categories) of HIV-infected patients had significantly higher circulating IL-10 levels than controls, with the highest levels among the AIDS patients, particularly in patients with ongoing Mycobacterium avium complex (MAC) infection. Among 32 HIV-infected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
124
3
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(142 citation statements)
references
References 41 publications
12
124
3
3
Order By: Relevance
“…However, it should be noted that a direct comparison between these results is not possible due to the differences in the sampling period in the two studies (eclipse phase vs. acute/recent stage of infection). Stylianou et al showed increasing levels of IL-10 and TNF-α level in HIV-infected patients, regardless of the stage of infection but with highest concentrations in patients with the most advanced disease [27]. Our study also demonstrated increased concentrations of IL-10 and TNF-α in HIV-infected patients in both acute and chronic stage of infection compared to controls.…”
Section: Discussionsupporting
confidence: 76%
“…However, it should be noted that a direct comparison between these results is not possible due to the differences in the sampling period in the two studies (eclipse phase vs. acute/recent stage of infection). Stylianou et al showed increasing levels of IL-10 and TNF-α level in HIV-infected patients, regardless of the stage of infection but with highest concentrations in patients with the most advanced disease [27]. Our study also demonstrated increased concentrations of IL-10 and TNF-α in HIV-infected patients in both acute and chronic stage of infection compared to controls.…”
Section: Discussionsupporting
confidence: 76%
“…19 Even though the effect of HAART treatment during dengue infection remains unknown, the attenuation of certain cytokines in HIV-1-infected patients treated with HAART, such as IL-10 and TNF-α, could play an important role in decreasing dengue disease progression in HIV-1-positive patients. 20,21 Both IL-10 and TNF-α are strongly associated with severe dengue infection. 22 The HIV-1 viral loads in our patient remained at normal levels (< 40 HIV-1 RNA copies/mL) during DENV-1 infection and 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines have been shown to modulate the expression of NK receptors and some, such as TGF-␤, which down-regulates the levels of NKp30 (32), and IL-10, which increases the expression of several iNKRs (33), have been found to be present at elevated levels in the serum of AIDS patients (34)(35)(36). We did not find significant differences in the levels of TGF-␤ (13) or IL-10 (data not shown) secreted by NK cells from viremic individuals compared with those of healthy donors, suggesting that at least an autocrine mechanism of receptor modulation among NK cells is not likely.…”
Section: Discussionmentioning
confidence: 99%